Oxygen Profiles Across the Sea-Surface Microlayer—Effects of Diffusion and Biological Activity - Rahlff, Janina; Stolle, Christian; Giebel, Helge-Ansgar; Ribas-Ribas, Mariana; Damgaard, Lars Riis; Wurl, Oliver (Frontiers in Marine Science, 2019)
Gas exchange across the air-water interface is strongly influenced by the uppermost water layer (<1 mm), the sea-surface microlayer (SML). However, a clear understanding about how the distinct physicochemical and biological properties of the SML affect gas exchange is lacking. We used an automatic microprofiler with Clark-type microsensors to measure small-scale profiles of dissolved oxygen in the upper 5 cm of the water column in a laboratory tank filled with natural seawater. We aimed to link changing oxygen concentrations and profiles with the metabolic activity of plankton and neuston, i.e. SML-dwelling organisms, in our artificial, low-turbulence set-up during diel cycles. We observed that temporal changes of the oxygen concentration in near surface water (5 cm depth) could not be explained by diffusive loss of oxygen, but by planktonic activity. Interestingly, no influence of strong neuston activity on oxygen gradients at the air-water interface was detectable. This could be confirmed by a modeling approach, which revealed that neuston metabolic activity was insufficient to create distinct curvatures into these oxygen gradients. Moreover, the high neuston activity in our study contributed only less than 7% to changes in oxygen concentration in the tank. Overall, this work shows that temporal and vertical variation of oxygen profiles across the air-water interface in controlled laboratory set-ups is driven by biological processes in the underlying bulk water, with negligible effects of neuston activity.